The effects of in vivo passaging, solar radiation exposure and inoculum dose on the genetic diversity of Helicoverpa armigera nucleopolyhedrovirus - Kitchin, Dale John (My University, 2017)
The nucleopolyhedroviruses (NPVs) are a group of entomopathogenic viruses, with large double-stranded DNA genomes, which belong to the Baculoviridae family. Considerable genetic diversity is known to exist within NPV populations, with a number of studies having shown that NPV populations consist of multiple genotypes. Studies have also shown that the genotypic composition of NPV populations can vary between different host individuals and geographical locations. Yet, how this genetic diversity is generated and maintained in NPV populations over successive infections is not fully understood. In this study, a denaturing gradient gel electrophoresis (DGGE) assay and deep amplicon sequencing were used to assess the effects of serial in vivo passaging, pre-infection exposure to solar radiation and occlusion derived virion (ODV) inoculum dose on the genetic diversity of Helicoverpa armigera nucleopolyhedrovirus (HearNPV) populations within regions of the DNA polymerase and me53 genes. The serial in vivo passaging of a HearNPV population, using a high OB inoculum dose (LD90 × 5), did not result in a common or similar genotypic composition in the 125 third passage HearNPV populations isolated from individual host insects. Shifts in the relative abundance of inoculum genetic variants and the generation of novel genetic variants caused the HearNPV populations isolated from individual insects to diverge in genetic variant composition over the three serial in vivo passages. Although pre-infection exposure of HearNPV OBs to solar radiation did not increase the frequency at which novel genetic variants were generated over the course of an infection, it did appear to contribute to the divergence in genetic variant composition of HearNPV populations over in vivo passages. It was also observed that the higher the ODV inoculum dose the greater the probability that the genetic variant composition of the post-passage HearNPV population would resemble that of the inoculum population. Overall it was shown that in vivo passaging, pre-infection exposure of OBs to solar radiation and ODV inoculum dose all affect the genotypic composition of HearNPV populations. The findings of this study contribute to the understanding of the factors that affect the generation and maintenance of HearNPV genetic diversity over the course of an infection and provide insights into how the genetic diversity between distant geographical HearNPV isolates may develop in the field.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy, Johannesburg 2017
Keywords: Helicoverpa armigera; Insects--Viruses